Contrast‐enhanced spectral mammography: A potential exclusion diagnosis modality in dense breast patients. (19th February 2020) - Qin, Yun; Liu, Ying; Zhang, Xueqin; Zhao, Shuang; Zhong, Huanhuan; Huang, Juan; Yu, Jianqun
Abstract: Background: China has an increasing burden of breast cancer. However, with a large population of dense breast patients, the diagnostic efficiency of conventional digital mammography is attenuated. Methods: From July 2017 to October 2018, we retrospectively reviewed 397 dense breast patients who underwent contrast‐enhanced spectral mammography (CESM) in West China Hospital. Among them, 53 patients who had both CESM and dynamic contrast enhanced magnetic resonance imaging (DCE‐MRI) results and 114 patients who had pathological diagnoses were finally enrolled. All images were reviewed by two independent radiologists according to the 2013 Breast Imaging Reporting and Data System (BI‐RADS) with all disagreements handed to an associate professor for final decisions. Correlation analyses between CESM and DCE‐MRI were conducted. The diagnostic performance of CESM were investigated. Results: The kappa value of the BI‐RADS scores between CESM and DCE‐MRI was 0.607 ( P  < .001), indicating high correspondence between CESM and DCE‐MRI. As for lesion size measurement, moderate correlation (Kendall's tau coefficient: 0.556, P  < .001) was detected between CESM and DCE‐MRI. Using pathological diagnoses as the reference standard, the sensitivity, specificity, and area under the curve (AUC) of CESM were 82.4%, 96.4%, and 0.894, respectively. Conclusion: CESM demonstrated excellent overall diagnostic accuracy and a moderate correlation in lesion size estimation against DCE‐MRI in dense breast patients, supporting it to be an alternative to DCE‐MRI in breast cancer detection and diagnosis, especially for exclusion diagnosis. Abstract : China has an increasing burden of breast cancer, but with a population of dense breast patients, the diagnostic efficiency of conventional digital mammography was attenuated. Our study suggested that CESM exhibited an excellent diagnostic efficiency and a moderate correlation in lesion size estimation compared to DCE‐MRI and pathology, supporting it to be an alternative to DCE‐MRI in breast cancer detection and diagnosis, especially for exclusion diagnosis in dense breast patients.